2015
DOI: 10.4103/0300-1652.160360
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section and perinatal outcomes in a sub-urban tertiary hospital in North-West Nigeria

Abstract: Objectives:This study was undertaken to review the caesarean section rate and perinatal mortality in Federal Medical Centre, Birnin Kudu from 1st January 2010 to 31st December, 2012.Materials and Methods:This was a retrospective study involving review of 580 case files. Ethical clearance was obtained. The records of labour ward, neonatal intensive care unit (ICU) and operating theatre were use. Information extracted includes age, parity, booking status, total deliveries, indications for caesarean section and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…[12][13][14][15][16] Similar patterns were reported from the studies done in Sokoto, Gwagwalada, Zaria, Gombe, Maiduguri, Birnin Kebbi, Birnin Kudu, Sagamu, Lagos, Awka and Jos. [17][18][19][20][21][22][23][24][25][26]28 It was found that, among the leading indications for elective caesarean section in this study were previous caesarean section, breech presentation, suspected fetal macrosomia, abnormal lie and presentation, and twin and higher order multiple pregnancies which are a common trend. Some (5.6%) of the elective caesarean sections were done for prevention of mother to child transmission of HIV; this is relatively high, close to the 7.34% reported in Calabar and reflective of the prevalence of HIV in the south-south region of the country.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[12][13][14][15][16] Similar patterns were reported from the studies done in Sokoto, Gwagwalada, Zaria, Gombe, Maiduguri, Birnin Kebbi, Birnin Kudu, Sagamu, Lagos, Awka and Jos. [17][18][19][20][21][22][23][24][25][26]28 It was found that, among the leading indications for elective caesarean section in this study were previous caesarean section, breech presentation, suspected fetal macrosomia, abnormal lie and presentation, and twin and higher order multiple pregnancies which are a common trend. Some (5.6%) of the elective caesarean sections were done for prevention of mother to child transmission of HIV; this is relatively high, close to the 7.34% reported in Calabar and reflective of the prevalence of HIV in the south-south region of the country.…”
Section: Discussionmentioning
confidence: 97%
“…In teaching hospitals, documented caesarean section rate was 30.3% in Port Harcourt, 25.6% in Calabar, 27.6% in Enugu, 18.5% in Nnewi, 16.4% in Abakaliki, 11.3% in Sokoto, 21.4% in Abuja, 24.5% in Zaria, 19.8% in Gombe, 11.8% in Maiduguri, 17.69% in Birnin Kudu, 20.3% in Birnin Kebbi, 32.9% in Sagamu, and 40.1% in Lagos. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] In general hospitals, 10.4% was documented in Awka and 5.39% in Calabar, while a private hospital in Jos recorded 8.9%. [26][27][28] This trend exists despite a population level rate as low as 2%, suggesting that assess to caesarean section is skewed; whereas a lot of women lack access to caesarean section to save their lives and that of their babies, some might be undergoing unnecessary procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural beliefs and negative attitudes towards CS are other possible explanations for a delay in care-seeking behaviour and low CS rate [17,18]. As a result, the population CS rate remains low at 2.7% [11] and between 11 and 49% in facilities [19][20][21][22], with positive associations between likelihood of CS and urban residence [23], wealth and higher education level [24,25]. Extremely low CS rates of 0.4% are found among the poorest women [24].…”
Section: Introductionmentioning
confidence: 99%
“…While the evidence of the effect of socio-economic status and place of residence on CS rates in Nigeria is well established, little is known about CS rates in relation to obstetric needs. A few facility-based studies have shown increased odds of having a CS for women with overweight, previous CS [21] and obstructed labour [22]. Only one population-based study has investigated the association between obstetric factors and CS in Nigeria using the 2013 Demographic and Health Survey (DHS) data, showing a positive association between CS and maternal age, large birth size, multiple pregnancy, primiparity, health insurance coverage, antenatal care (ANC) and maternal obesity [26].…”
Section: Introductionmentioning
confidence: 99%
“…It is being thought that severe military conflicts in Africa shorten the expected lifetime for more than 2 years. In general, WHO had calculated that 269 thousand people had died in 1999 due to the effect of wars and that loss of 8.44 million healthy years of life had occurred (2,3). Wars negatively affect the provision of health services.…”
Section: War and Women's Healthmentioning
confidence: 99%